Hubungan Faktor Internal dengan Perolehan Belajar Siswa SMU - Sihkabuden Sihkabuden (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This is a study on the correlation between the four variables of cognitive styles, learning habits, achievement motivation, and locus of control and students’ achievement in mathematics, physics, Indonesian, English, economics, and geography. The data were collected through tests and documentation. The results indicated that there were positive correlations between cognitive styles, learning habits, achievement motivation, and locus of control and the students’ achievement. There were also significant correlations among these predictor variables: (1) between cognitive styles and learning habits and (2) between achievement motivation and locus of control. The path analysis indicated that the four predictable variables had effects on the students’ achievement.